Chemosensitivity Testing in Oncology - Reinhold, Uwe (Springer, 2003)
The last decade has seen a renaissance of the concept of individualized chemotherapy in oncology, markedly stimulated by the development of new in vitro chemosensitivity assays. The clinical utility of drug response assays has been evaluated in clinical trials and the results suggest that assay-assisted therapy selection may improve survival as well as economic outcomes. This volume comprises the proceedings of the first Symposium of the International Society for Chemosensitivity Testing in Oncology, ISCO-1, held in Homburg/Saar, Germany, in September 2001. The topics include: new in vitro drug-testing methods, tumor chemosensitivity assays, and the clinical relevance of assay-directed therapy